2015
DOI: 10.1016/j.fertnstert.2015.07.1151
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin dose is negatively correlated with live birth rate: analysis of more than 650,000 assisted reproductive technology cycles

Abstract: Objective To evaluate the correlation between total gonadotropin dose and live birth rate Design Retrospective analysis Setting Clinic-based data Patients 658,519 fresh autologous cycles of in vitro fertilization (IVF) reported to the Society for Assisted Reproductive Technology from 2004 to 2012 Interventions None Main outcome measures Logistic regression models were fitted to live birth rates using categorized values for total follicle stimulating hormone (FSH) dose and number of oocytes retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
69
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 54 publications
14
69
0
2
Order By: Relevance
“…Corroborating evidence is also provided by the study of Baker et al (2015), showing that live birth rates diminish with increasing dosage of gonadotrophins, nearly independently of maternal age (Baker et al, 2015). Taken together, it may be speculated that differences in donor ovarian stimulation regimens used by different treating centers in this study may be a contributing factor to the observed differences in euploidy rates.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Corroborating evidence is also provided by the study of Baker et al (2015), showing that live birth rates diminish with increasing dosage of gonadotrophins, nearly independently of maternal age (Baker et al, 2015). Taken together, it may be speculated that differences in donor ovarian stimulation regimens used by different treating centers in this study may be a contributing factor to the observed differences in euploidy rates.…”
Section: Discussionsupporting
confidence: 63%
“…Physicians may have individual preferences for FSH dosage for donors and the number of eggs they aim to collect. Higher FSH dosages in the presence of normal ovarian response may be associated with poorer outcomes (Baker et al, 2015), which may be oocyte quality related. Physicians may also follow different routines during follicle aspiration, for example which follicles they choose to aspirate and at what negative pressure, whether they tend to flush follicles or not, and differences in time between hCG administration and egg retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors affecting the endometrium and uterine environment may also be associated with adverse outcomes. Both gonadotropin dose and number of oocytes retrieved are associated with reduced live birth rates and decrements in birthweight (62, 63). …”
Section: Discussionmentioning
confidence: 99%
“…From a registry-based retrospective analysis of 658,519 SART reported (2004-2012) fresh autologous IVF cycles, the analysis showed that poor responders (i.e., 1-5 oocytes), whether from low (<1000 IU FSH) or high (>5000 IU FSH) total FSH dose cycles, had reduced pregnancy compared normal responders (i.e., 11-15 oocytes) with similar ovarian stimulation, 21.7 versus 46.5 % and 12.5 versus 26.2 %, respectively [32]. The results of this study, however, exposes the notion held by many that pregnancy outcomes in poor ovarian responders are necessarily always severely reduced, with pregnancy rates of >50 % achieved in cycles with successful blastocyst culture and transfer, especially if transferred in FET.…”
Section: Discussionmentioning
confidence: 99%